Guinea : Fifth and Sixth Reviews Under the Extended Credit Facility Arrangement, Financing Assurances Review, and Request for Waivers of Nonobservance of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Guinea. (IMF Staff Country Reports; Country Report, 2020)
Real growth is expected to reach 5.2 percent in 2020 as the severe impact of the pandemic in the country was partially mitigated by a resilient mining sector. Presidential elections were held on October 18, giving President Conde an outright victory. Such results were contested by the opposition and followed by violent demonstrations and unrest. Since the Constitutional Court validated the electoral results on November 7, the situation has remained calm.